Intestinal Microbiocenosis Disorders Correction With Intestinal Lavage in Patients With Acute Poisoning - V. A. Matkevich; M. M. Potskhveriya; A. Yu. Simonova; T. A. Vasina; S. S. Petrikov (Неотложная медицинская помощь, 2021)
Background. In acute poisoning, accompanied by a violation of microbiocenosis, the problem of its correction has not been studied enough.Aim of study. Evaluate the possibility of correcting violations of microbiocenosis using intestinal lavage in cases of poisoning with psychopharmacological preparations and cauterizing substances.Material and methods. 50 male (76.4%) and female (23.6%) patients aged 42 (36; 52) years with psychopharmacological drugs and cauterizing substances poisoning were examined, the composition of the fecal microflora was studied. A total of 100 studies of up to 10 species of microorganisms were conducted. In order to correct violations of the species composition of microbiocenosis, 30 patients underwent intestinal lavage. The comparison group included 20 patients who did not use intestinal lavage.Results. In patients with these poisonings, violations of the specific microbial composition of feces were detected. Intestinal lavage, in contrast to standard therapy, had a corrective effect on fecal microbiocenosis.Conclusion. With the help of intestinal lavage, it is possible to correct violations of microbiocenosis in acute poisoning in a short time.